Ranging Patterns of Critically Endangered Colobine, Presbytis chrysomelas chrysomelas - Ahmad Ampeng; Badrul Munir Md-Zain (The Scientific World Journal)
Presbytis chrysomelas chrysomelas endemic only in Sarawak and Kalimantan was categorized by IUCN as a critically endangered primate that require special attention from research and conservation perspectives. A qualitative study on ranging patterns of P. c. chrysomelas was conducted in the Samunsam Wildlife Sanctuary, Sarawak. The study was conducted over a period of 13 months from December 2004 to December 2005 with 213 days of observation. Behavioural observation covered 17 groups with special emphasis on two main groups and 1 subadult group. Scanning and focal sampling were employed as the observation methods. Results indicated that P. c. chrysomelas had vertical, straight horizontal, and cross-horizontal types of movement patterns. P. c. chrysomelas was recorded to have a short movement distance (31.8–54.3 m). Distribution, abundance types, and food resources might be the factors that shaped the patterns of movement and distance in P. c. chrysomelas.